Greenland, Kejser Franz Joseph Fjord - Boyd, Louise Arner, 1887-1972 (1931)
August 12, 1931. Segelsallskapets Fjord. Berzelius Berg. Photo taken near Cape Maechel - the eastern point of land which forms the junction where Forsblads Fjord goes to the N.W. Alp Fjord to the S.E. and the very large fjord - Segelsallskapets Fjord - go N.E. from Cape Maechel to King Oscar Fjord. Berzelius Berg is here seen facing south and southwest on the north side of Segelsallskapets Fjord.